Elastoplastic Analysis of Shear Behavior of Multicell Shaped Concrete-Filled Steel Tubular Connection Based on Unified Theory - Xi Chen; Jianyang Xue (Advances in Civil Engineering)
Connection between multicell shaped concrete-filled steel tube (MCFST) columns and steel beams gives full play of strength and properties of steel tube and core concrete and has many advantages in mechanical and seismic performance. Shear behavior of the connection is crucial to damage performance of special-shaped CFST structure under seismic load. However, few studies focused on shear behavior of the MCFST connection. This study investigates elastoplastic shear behavior of the MCFST connection. Nine specimens were tested under constant axial load and lateral low cyclic loading. The test results showed that as height to thickness ratio of column section increased, the plastic status of the stresses of the flange limb steel webs was obviously different from those of the web limb steel webs, and initial shear stiffness of the panel zone increased. In order to give analytical methods for shear behavior of the MCFST connection under compressive and shear force at the material level to engineers, according to unified theory the analytical model of MCFST composite material in the panel zone is equivalent to that of concrete-filled circular steel tube of web and flange limbs considering the difference of the stresses of the steel webs and interaction between the web and flange limbs. Based on the previous research and analysis of test results, migration and evolution are carried out from analytical models for shear behavior of the MCFST connection at the material level to that at the member level. The analytical expression of initial shear stiffness of the MCFST connection is derived, and the theoretical results correlate well with the experimental results. In addition, the analytical expression of shear stiffness of the MCFST connection in plastic hardening stage is obtained. The calculation formulas are proposed to predict the shear stiffness of the MCFST connection in the elastic and plastic hardening stages by geometrical parameters, material property parameters, and stress state of the steel webs.